Association between Signal Hyperintensity on T1-Weighted MR Imaging of Carotid Plaques and Ipsilateral Ischemic Events - Yamada, N.; Higashi, M.; Otsubo, R.; Sakuma, T.; Oyama, N.; Tanaka, R.; Iihara, K.; Naritomi, H.; Minematsu, K.; Naito, H. (American Journal of Neuroradiology, 2007)
BACKGROUND AND PURPOSE: To investigate associations between cerebral ischemic events and signal hyperintensity in T1-weighted MR imaging (T1WI) of carotid plaque according to stenosis severity and to estimate persistence of T1WI signal hyperintensity.METHODS: A total of 222 patients (392 atherosclerotic carotid arteries) underwent plaque imaging using 3D inversion-recovery-based T1WI (magnetization-prepared rapid acquisition with gradient-echo [MPRAGE]). Carotid plaque with intensity on MPRAGE of >200% that of adjacent muscle was categorized as “high signal intensity” and correlated with ipsilateral ischemic events within the previous 6 months. A total of 58 arteries (35 patients) underwent repeat MR imaging a total of 70 times at a median interval of 279 days (range, 10–1037 days).RESULTS: Ipsilateral ischemic events were more frequent in patients with MPRAGE high signals than in patients with low signals in the 0%–29%, 30%–69%, and 70%–99% stenosis groups: Relative risk (95% confidence interval) was 2.50 (0.96–6.51), 7.55 (1.84–31.04), and 1.98 (1.01–3.90), respectively. In the 70 cases of repeat MR imaging, 29 of 30 cases with high signals on the preceding MR imaging maintained high signals. Of the 58 arteries that underwent repeat MR imaging, 4 of 22 carotid arteries with high signals developed ipsilateral subsequent ischemic events within 1 year, whereas none with low signals developed subsequent events.CONCLUSIONS: Carotid plaque signal hyperintensity on T1WI is strongly associated with previous ipsilateral ischemic events, persisting over a period of months, and may indicate risk of subsequent events. Larger clinical trials are warranted to clarify associations between signal hyperintensity and risk of subsequent cerebral ischemic events.